2017
DOI: 10.1016/j.jcol.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Deoti surgical flap and sphincteroplasty for treatment of severe perineal deformity

Abstract: Purpose Anal incontinence is a very stigmatizing condition, which affects biopsychosocially the patient. It is a neglected, but quite common complication of obstetric and anorectal surgery, however it has treatment options. None of the treatment options have exceptional efficacy rates and still associated with risk of recurrence. The surgery techniques known are: anterior and posterior shortening procedure; post-anal repair; anterior elevator plasty and external sphincter plication; total pelvic floor repair a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…This contact prevents extensive fibrosis and adhesion of the skin fibrosis to the muscle tissue, due to many stem and progenitor cells present in subcutaneous fat. 5 Our study aims to provide a useful report for the future treatment of severe perineal deformity, which is fortunately rare, giving us a small number of cases. These cases showed that the Deoti's flap had important and positive impacts on the patient's scores.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contact prevents extensive fibrosis and adhesion of the skin fibrosis to the muscle tissue, due to many stem and progenitor cells present in subcutaneous fat. 5 Our study aims to provide a useful report for the future treatment of severe perineal deformity, which is fortunately rare, giving us a small number of cases. These cases showed that the Deoti's flap had important and positive impacts on the patient's scores.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical technique used, described in details at Rodrigues, Buzatti et al, 5 is based on the principle for an optimal suture ( Fig. 1) and the benefits of fat grafting.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation